Improving the supply chain of motor pumps to accelerate mechanized small-scale private irrigation in Zambia - Colenbrander, W.; van Koppen, Barbara (Informa UK Limited, 2013)
During the past decade, smallholder groundwater irrigation with motor pumps has increased considerably in Zambia. This study analyzes an important but hitherto ignored factor for adoption: the supply chain of imported motor pumps. The main obstacles for farmers are identified as: the highly centralized supply chain and financing facilities in urban hubs; lack of information about prices, which vary significantly for the same make and model of pump; lack of information and training on proper use and maintenance; and lack of financing facilities. The Zambia National Farmers Union seems best placed to remove these obstacles.